Emergency contraception knowledge level and e-health literacy in Turkish university students - Filiz Aslantekin-Özcoban; Mukadder Gün (IMR Press, 2021)
Background: Unwanted pregnancy is a serious problem, especially considering its impact on the lives of young people. Currently, emergency contraception (EC) is an effective method to prevent unwanted pregnancies that result in unsafe abortions and harm women's health. It is essential that university students, one of the risk groups for unwanted pregnancies, be familiar with this method. The aim of this study is to determine university students' knowledge of emergency contraception, influencing factors and e-health literacy levels. Methods: The cross-sectional study was conducted on 1003 senior undergraduate students at a public university. Data were collected via a Personal Information Form, Emergency Contraception Test, and e-Health Literacy Scale. For data analysis, descriptive analyses, t-test, ANOVA/Pearson correlation tests were used. Results: The e-HL score mean of students was found to be 25.68 ± 7.0. EC knowledge scores of students were 5.7 ± 2.8 for female students and lower for male students (4.3 ± 2.0). There was a significant difference between the groups in terms of EC knowledge scores in favor of women (p < 0.05). EC knowledge score of those who received reproductive health education was 5.8 ± 3.1, significantly higher than those who did not (p < 0.05). The knowledge score of those whose EC information source was an advisor/lecturer was significantly higher than those receiving information from other sources (p < 0.05). Scores on knowledge of emergency contraception were found to be significantly correlated positively with e-Health literacy scores (p = 0.00). Conclusion: Improved e-health literacy of students can be key to improving their knowledge of emergency contraception.